Immune reconstitution after autologous hematopoietic stem cell transplantation - João, Cristina Maria Pires (2007)
Abstract The investigation of the web of relationships between the different elements of the immune system has proven instrumental to better understand this complex biological system. This is particularly true in the case of the interactions between B and T lymphocytes, both during cellular development and at the stage of cellular effectors functions. The understanding of the B–T cells interdependency and the possibility to manipulate this relationship may be directly applicable to situations where immunity is deficient, as is the case of cancer or immune suppression after radio and chemotherapy. The work presented here started with the development of a novel and accurate tool to directly assess the diversity of the cellular repertoire (Chapter III). Contractions of T cell receptor diversity have been related with a deficient immune status. This method uses gene chips platforms where nucleic acids coding for lymphocyte receptors are hybridized and is based on the fact that the frequency of hybridization of nucleic acids to the oligonucleotides on a gene chip varies in direct proportion to diversity. Subsequently, and using this new method and other techniques of cell quantification I examined, in an animal model, the role that polyclonal B cells and immunoglobulin exert upon T cell development in the thymus, specifically on the acquisition of a broader repertoire diversity by the T cell receptors (Chapter IV and V). The hypothesis tested was if the presence of more diverse peptides in the thymus, namely polyclonal immunoglobulin, would induce the generation of more diverse T cells precursors. The results obtained demonstrated that the diversity of the T cell compartment is increased by the presence of polyclonal immunoglobulin. Polyclonal immunoglobulin, and particularly the Fab fragments of the molecule, represent the most diverse self-molecules in the body and its peptides are presented by antigen presenting cells to precursor T cells in the thymus during its development. This probably contributes significantly to the generation of receptor diversity. Furthermore, we also demonstrated that a more diverse repertoire of T lymphocytes is associated with a more effective and robust T cell immune function in vivo, as mice with a more diverse T cell receptors reject minor histocompatiblility discordant skin grafts faster than mice with a shrunken T cell receptor repertoire (Chapter V). We believe that a broader T cell receptor diversity allows a more efficient recognition and rejection of a higher range of external and internal aggressions. In this work it is demonstrated that a reduction of TCR diversity by thymectomy in wild type mice significantly increased survival of H-Y incompatible skin grafts, indicating decrease on T cell function. In addiction reconstitution of T-cell diversity in mice with a decreased T cell repertoire diversity with immunoglobulin Fab fragments, lead to a increase on TCR diversity and to a significantly decreased survival of the skin grafts (Chapter V). These results strongly suggest that increases on T cell repertoire diversity contribute to improvement of T cell function. Our results may have important implications on therapy and immune reconstitution in the context of AIDS, cancer, autoimmunity and post myeloablative treatments. Based on the previous results, we tested the clinical hypothesis that patients with haematological malignancies subjected to stem cell transplantation who recovered a robust immune system would have a better survival compared to patients who did not recover such a robust immune system. This study was undertaken by the examination of the progression and overall survival of 42 patients with mantle cell non-Hodgkin lymphoma receiving autologous hematopoietic stem cell transplantation (Chapter VI). The results obtained show that patients who recovered higher numbers of lymphocytes soon after autologous transplantation had a statistically significantly longer progression free and overall survivals. These results demonstrate the positive impact that a more robust immune system reconstitution after stem cell transplantation may have upon the survival of patients with haematological malignancies. In a similar clinical research framework, this dissertation also includes the study of the impact of recovering normal serum levels of polyclonal immunoglobulin on the survival of patients with another B cell haematological malignancy, multiple myeloma, after autologous stem cell transplantation (Chapter VII). The relapse free survival of the 110 patients with multiple myeloma analysed was associated with their ability to recover normal serum levels of the polyclonal compartment of immunoglobulin. These results suggest again the important effect of polyclonal immunoglobulin for the (re)generation of the immune competence. We also studied the impact of a robust immunity for the response to treatment with the antibody anti CD20, rituximab, in patients with non- Hodgkin’s lymphoma (NHL) (Chapter VIII). Patients with higher absolute counts of CD4+ T lymphocytes respond better (in terms of longer progression free survival) to rituximab compared to patients with lower number of CD4+ T lymphocytes. These observations highlight again the fact that a competent immune system is required for the clinical benefit of rituximab therapy in NHL patients. In conclusion, the work presented in this dissertation demonstrates, for the first time, that diverse B cells and polyclonal immunoglobulin promote T cell diversification in the thymus and improve T lymphocyte function. Also, it shows that in the setting of immune reconstitution, as after autologous stem cell transplantation for mantle cell lymphoma and in the setting of immune therapy for NHL, the absolute lymphocyte counts are an independent factor predicting progression free and overall survival. These results can have an important application in the clinical practice since the majority of the current treatments for cancer are immunosuppressive and implicate a subsequent immune recovery. Also, the effects of a number of antineoplastic treatments, including biological agents, depend on the immune system activity. In this way, studies similar to the ones presented here, where methods to improve the immune reconstitution are examined, may prove to be instrumental for a better understanding of the immune system and to guide more efficient treatment options and the design of future clinical trials. Resumo O estudo da rede de inter-relações entre os diversos elementos do sistema immune tem-se mostrado um instrumento essencial para uma melhor compreensão deste complexo sistema biológico. Tal é particularmente verdade no caso das interacções entre os linfócitos B e T, quer durante o desenvolvimento celular, quer ao nível das funções celulares efectoras. A compreensão da interdependência entre linfócitos B e T e a possibilidade de manipular esta relação pode ser directamente aplicável a situações em que a imunidade está deficiente, como é o caso das doenças neoplásicas ou da imunossupressão após radio ou quimioterapia. O trabalho apresentado nesta dissertação iniciou-se com o desenvolvimento de um novo método laboratorial para medir directamente a diversidade do reportório celular (Capítulo III). Reduções da diversidade do reportório dos receptores de células T têm sido relacionadas com um estado de imunodeficiência. O método desenvolvido utiliza “gene chips”, aos quais hibridizam os ácidos nucleicos codificantes das cadeias proteicas dos receptores linfocitários. A diversidade é calculada com base na frequência de hibridização do ácido nucleico da amostra aos oligonucleótidos presentes no “gene chip”. De seguida, e utilizando este novo método e outras técnicas de quantificação celular examinei, num modelo animal, o papel que as células policlonais B e a imunoglobulina exercem sobre o desenvolvimento linfocitário T no timo, especificamente na aquisição de um reportório diverso de receptores T (Capítulos IV e V). Testei, então, a hipótese de que a presença no timo de péptidos mais diversos, como a imunoglobulna policlonal, induzisse a génese de precursores T mais diversos. Demonstrámos que a diversidade do compartimento T é aumentado pela presença de imunoglobulina policlonal. A imunoglobulina policlonal, e particularmente os fragmentos Fab desta molécula, representam as moléculas autólogas mais diversas presentes nos organismos vertebrados. Estes péptidos são apresentados por células apresentadoras de antigénio às células precursoras T no timo, durante o desenvolvimento celular T. Tal, provavelmente, contribui para a génese da diversidade dos receptores. Também demonstrámos que a presença de um reportório mais diverso de linfócitos T se associa a um incremento da função imunológica T in vivo. Uma diversidade de receptores T mais extensa parece permitir um reconhecimento e rejeição mais eficientes de um maior número de agressores internos e externos. Demonstrámos que ratinhos com receptores de células T (RCT) com maior diversidade rejeitam transplantes cutâneos discordantes para antigénios minor de histocompatibilidade mais rapidamente do que ratinhos com um menor reportório T (Capítulo V). Por outro lado, uma redução da diversidade do RCT, causada por timectomia de ratinhos de estirpes selvagens, mostrou aumentar significativamente a sobrevivência de transplantes cutâneos incompatíveis para o antigénio H-Y (antigénio minor de histocompatibilidade), indicando uma diminuição da função linfocitária T. Além disso, a reconstituição da diversidade dos linfócitos T em ratinhos com uma diversidade de reportório T diminuída, induzida pela administração de fragmentos Fab de imunoglobulina, conduz a um aumento da diversidade dos RCT e a uma diminuição significativa da sobrevivência dos enxertos cutâneos (Capítulo V). Estes resultados sugerem que o aumento do reportório de células T contribui para uma melhoria das funções celulares T e poderão ter implicações importantes na terapêutica e reconstitutição imunológica em contexto de SIDA, neoplasias, autoimunidade e após tratamentos mieloablativos. Baseado nos resultados anteriores, decidimos testar a hipótese clínica de que doentes com neoplasias hematológicas sujeitos a transplantação de precursores hematopoiéticos e com recuperação imunológica precoce após transplante teriam uma sobrevivência mais longa do que doentes que não recuperassem tão bem a sua imunidade. Analisámos a sobrevivência global e sobrevivência sem doença de 42 doentes com linfoma não Hodgkin de células do manto sujeitos a transplante autólogo de precursores hematopoiéticos (Capítulo VI). Os resultados obtidos mostraram que os doentes que recuperaram contagens mais elevadas de linfócitos imediatamente após o transplante autólogo, apresentaram uma sobrevivência global e sem progressão mais longa do que doentes que não recuperaram contagens linfocitárias tão precocemente. Estes resultados demonstram o efeito positivo de uma reconstitutição imunológica robusta após transplante de presursores hematopoiéticos, sobre a sobrevivência de doentes com neoplasias hematológicas. Do mesmo modo, estudámos o efeito que a recuperação de níveis séricos normais de imunoglobulina policlonal tem na sobrevivência de doentes com outras neoplasias hematológicas de linfócitos B, como o mieloma múltiplo,após transplante autólogo de precursos hematopoiéticos (Capítulo VII). A sobrevivência livre de doença dos 110 doentes com mieloma múltiplo analizados está associada com a sua capacidade de recuperar níveis séricos normais do compartmento policlonal de imunoglobulina. Estes resultados pioneiros indicam a importância da imunoglobulina policlonal para a génese de competência imunológica. Também estudámos o impacto de um sistema imunitário eficiente sobre a resposta ao tratamento com o anticorpo anti CD20, ituximab, em doentes com linfoma não Hodgkin (LNH) (Capítulo VIII). Os resultados mostram que doentes com valores mais elevados de linfócitos T CD4+ respondem melhor (em termos de maior sobrevida livre de doença) ao rituximab, do que doentes com valores mais baixos. Estas observações ilustram a necessidade de um sistema imunitário competente para o benefício clínico da terapêutica com rituximab em doentes com LNH. Em conclusão, o trabalho apresentado nesta dissertação demonstra que as células B e a imunoglobulina policlonal promovem a diversidade das células T no timo e melhoram a função linfocitária T periférica. Concomitantemente, também demonstrámos que, no contexto de reconstituição imune, por exemplo, após transplante autólogo de precursores hematopoiéticos em doentes com linfomas de células do manto, o número absoluto de linfócitos é uma factor independente da sobrevivência. Os resultados demonstram, também, a importância dos valores de linfocitos T na resposta ao tratamento com rituximab no caso de doentes com LNH. O mesmo princípio se prova pelo facto de que doentes com mieloma múltiplo sujeitos a transplante autólogo de precursores hematopoiéticos que recuperam valores normais séricos de imunoglobulinas policlonais, terem melhores taxas de resposta em comparação com doentes que não recuperam valores normais de imunoglobulinas policlonais. Estes resultados podem ter importantes aplicações na prática clínica dado que a maioria dos tratamentos de doenças neoplásicas implica imunossupressão e, subsequente, recuperação imunológica. Estes estudos podem ser um instrumento fundamental para uma melhor compreensão do sistema imune e guiar uma escolha mais eficiente de opções terapêuticas bem como contribuir para a concepção de futuros estudos clínicos.